Cascading disposal for food waste by integration of hydrothermal carbonization and supercritical water gasification. (March 2022) - Yan, Mi; Liu, Jianyong; Yoshikawa, Kunio; Jiang, Jiahao; Zhang, Yan; Zhu, Gaojun; Liu, Yu; Hantoko, Dwi
Abstract: Supercritical water gasification (SCWG) has drawn great attention as one of the wet biomass conversion technologies. This study investigated a cascading energy recovery process by integrating hydrothermal carbonization (HTC) and SCWG, aiming to achieve the efficient disposal and conversion of HTC process water. The physicochemical characteristics of hydrochars produced by HTC at different temperatures and residence times were analyzed. An energy densified hydrochar with calorific value of 22.68 MJ/kg was obtained under 275 °C for 60 min. SCWG was adopted to efficiently achieve the conversion of HTC process water into H2 -rich syngas. The effect of reaction temperatures (360 °C, 420 °C, 480 °C), residence times (15 min, 30 min, 45 min) and, and alkali catalysts on gasification characteristics and contaminants removal performance were studied. The highest H2 production of 1151.26 mmol/L was obtained at 480 °C and 45 min with 5 wt% KOH. The highest TOC and COD removal efficiencies of 83.04% and 82.99% were achieved at 480 °C, 45 min, respectively. The efficiencies of SCWG were enhanced by HTC, and less CO2 were generated. This cascading energy recovery process efficiently achieves the conversion of food waste to solid fuel and provides possible optimization of SCWG process. Graphical abstract: Image 1